The Analysis of Grammatical and Textual Equivalence Used in The Translation of Paolini‘s Novel of “Inheritance” into Indonesian - Badi’atul Azmina (IAIN Salatiga, 2016)
This study examines kinds of grammatical and textual equivalence which are used by Poppy D. Chusfani in translating English into Indonesia language of Christopher Paolini‘s Novel of “Inheritance” as well as the most dominant equivalence used by Poppy D. Chusfani in translating English into Indonesia language of Christopher Paolini‘s Novel of “Inheritance”. This is descriptive qualitative research and the method of collecting data of this study are documentation and library research. The data in the novel which have been collected are classified into two kinds of equivalence; grammatical equivalence (number, gender, person, tense/aspect and voice) and textual equivalence (reference, substitution, ellipsis, conjunction and lexical cohesion). After analyzing and classifying the data, researcher discovered that there are 25 data of number, 27 data of gender, 38 data of person, 12 data of tense/aspect and 12 data of voice. Furthermore, researcher discovered that there are 33 data of reference, 9 data of substitution and ellipsis, 35 data of conjunction and 17 data of lexical cohesion.Those data presented are representative from all of the data in the novel, because the writer takes the data by its part among the translated sentences contained grammatical and textual (cohesion) equivalence. To sum up, the result shows that Poppy D. Chusfani uses all kinds of grammatical and textual (cohesion) equivalence, after all, grammatical equivalence of person is the most dominant data (38) used by Poppy D. Chusfani in translating English into Indonesia language of Christopher Paolini‘s Novel of “Inheritance”